Wildfire - Grey, Zane, 1872-1939 (Salt Lake City, UT : Project Gutenberg, 2000)
"Wildfire" by Zane Grey is a novel written during the early 20th century, capturing the spirit of the American West. The story revolves around the character Lucy Bostil, a strong-willed young woman who is deeply connected to the desert landscape around her home, Bostil's Ford. The narrative explores themes of love, ambition, and rivalry amidst the backdrop of horse racing and the desire for freedom, setting the stage for Lucy's impending adventures and conflicts, particularly concerning her father's prized racehorse, the Sage King. The opening of the novel introduces Lucy Bostil as she grapples with her feelings of longing and restlessness on her eighteenth birthday while riding a forbidden horse out on the sage. The text paints a vivid picture of Lucy's admiration for the natural beauty surrounding her and her love for horses, contrasting it with the constraints of civilization and her father$1 (Bs expectations. As she encounters various characters, including her father John Bostil and the rival Joel Creech, the stage is set for action and conflict. The dynamics of competition, particularly a contentious race between Bostil's Sage King and Creech's Blue Roan, establish tension within the community, making it clear that Lucy's future is intricately tied to these rivalries and her own aspirations for independence. (This is an automatically generated summary.)s
Release date is 2000-02-01
Produced by Daniel Wentzell. HTML version by Al Haines.
Keywords: Utah -- Fiction; Wild horses -- Fiction